Comparative Analysis of Profit Sharing Financing Between Islamic Banks (BUS) and Rakyat Sharia Financing Bank (BPRS) in Indonesia - Yuliana, Saadah; Suhel, Suhel; Bashir, Abdul (International Journal of Economics and Financial Issues, 2017)
This study is a comparative empirical studies that discuss the distribution of funds in Islamic banking that use contract profit-sharing. Specifically, this study aimed to analyze the differences in the average funding for mudharabah results with profit sharing financing Musharaka agreement on the BUS and the BPRS. The data used secondary data with the period from July 2012 to July 2016. The study found that there is a significant difference between the average profit sharing financing using Mudharabah and Musharaka contract extended by BUS or distributed by the BPRS. The average funding channeled by BUS with Musharaka contract value is higher than its threefold Mudharabah financing. Average Musharaka financing disbursed by BPRS, higher value quadrupled funding channeled with Mudharabah. Keywords: Islamic Banks, Financing Analysis, Mudharabah, Musharaka. JEL Classifications: E50, G21, G32, M40